Analisis Tingkat Kelelahan Pada Mahasiswa yang Bekerja di Batam - Sri Zetli; Elsya Paskaria Loyda Tarigan; Nofriani Fajrah (LPPM Universitas Putera Batam, 2025)
The phenomenon of students choosing to work while completing their studies has become increasingly common in recent years. The decision to work while studying often presents unique challenges for students. Fatigue resulting from academic and work pressures is a common risk faced by students who are employed. On the one hand, students must fulfill their academic obligations, such as assignments, exams, and projects, which require significant time and concentration. On the other hand, work demands additional time and energy, often involving heavy targets and responsibilities. The combination of academic and professional demands can lead to fatigue among students who are not working. In this context, analyzing fatigue among working students is crucial. This study was conducted on students at one of the universities in Batam. Fatigue was measured using the Fatigue Assessment Scale (FAS) questionnaire. The results of data processing and analysis showed that 2.57% of students were in the very low fatigue category, 9.65% experienced low fatigue, 27.33% experienced moderate fatigue, 47.27% experienced high fatigue, and 13.18% experienced very high fatigue. The results of the Chi-Square test showed that only the level of education had an effect on fatigue, while gender, age, and program of study did not have a significant relationship. The results of the ANOVA test showed that the fatigue experienced by students who were working and studying did not differ by gender and program of study, while for age groups and levels of education, the fatigue experienced by students differed